A review on phyto active compounds of moringa for health benefits and as a resilience in climate change - Priya Kumari; S. Ramesh Kumar (Journal of Agriculture and Food Research)
The growth in air, water and soil pollution has become major danger for world's health, causing widespread sickness and untimely death. Soil health is critical for producing risk-free food, though it is jeopardized by toxic substances like heavy metals, pesticides, plastics and overfertilization, which lead to the loss of favorable microbes as well as adulteration in groundwater. Hydrological features are polluted by industrial effluents, domestic wastewater, agricultural runoff and oil spills, intensifying environmental harm. However, atmospheric pollution, which is defined as excessive release of gases, greenhouse gases and volatile chemicals, has a negative influence on the climate but also presents significant major health risks, including respiratory ailments, cardiovascular problems and an increased chance of developing cancer. Thus, the judicious use of conventional plants comes out as a powerful instrument for environmental rehabilitation and wellness enhancement. Plants have inherent filteration properties, eliminating toxins present in the air, water and soil, reducing their negative impacts. Plants may actively extract and eliminate toxins through phytoremediation, helping to detoxify and improve water and soil quality. Moringa oleifera, also recognized as the “miracle tree,” holds great potential for solving the many issues caused by the change in climate. The tree's exceptional heat tolerance and capacity to make a cooler microclimate makes it an excellent choice for hot and arid areas. Moringa's mechanisms of deep roots and effective water use allow it to survive in drought circumstances, thereby encouraging water conservation. Furthermore, moringa aids in pollution reduction by absorbing pollutants and CO2, cleaning water through its seeds and lowering soil toxins. Moringa is a nutritional and medicinal powerhouse that improves community health in addition to its environmental benefits. This analysis consolidates the discoveries of the past three decades and offers a comprehensive examination of the M. oleifera plant, covering its various parts and detailing its documented applications across environmental, health sectors, food and industrial.